Head-to-head competition does not affect pacing or performance in 1 km cycling time trials. Issue 1 (2nd January 2020) - Wood, Tiffany; Bui, Connor Thien Long; Lubbock, Connor; Wilson, Jason; Jeffrey, Scott; Lawrence, Mitchell; Leung, Colleen; Mashar, Darshit; Sims, Nicholas; Konings, Marco J.; Hettinga, Florentina J.
ABSTRACT: Previous research has shown enhanced performance and altered pacing behaviour in the presence of a virtual opponent during middle-distance cycling time trials with a duration of 2 min and longer. The purpose of this study was to determine whether these effects are also present in cycling time trials of shorter duration. Twelve physically active men completed three 1-km time trials. After a familiarisation trial (FAM), participants performed two experimental conditions: one without opponent (NO) and one with a virtual opponent (OP). Repeated-measures ANOVAs were used to assess differences in pacing and performance using power output and duration (p<0.05). No differences in mean finishing times (FAM: 91.5 ± 7.7 s; NO: 91.6 ± 6.4 s; OP: 90.9 ± 4.9 s; p=0.907) or power output (FAM: 382 ± 111 W; NO: 363 ± 80 W; OP: 367 ± 67; p=0.564) were found between experimental conditions. Furthermore, no differences in pacing profiles between experimental conditions were found (p=0.199). Similarly, rate of perceived exertion did not differ between experimental conditions at any moment (p=0.831). In conclusion, unlike events of a more prolonged duration (>2 min), the presence of an opponent did not affect participants' pacing behaviour in short duration 1-km time trials.